2006
DOI: 10.1007/s11255-006-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Does aflatoxin as an environmental mycotoxin adversely affect the renal and hepatic functions of Egyptian lactating mothers and their infants? A preliminary report

Abstract: Mothers and their infants in our locality showed a relatively high aflatoxin contamination rate. We did not find a correlation of this contamination level and either renal or hepatic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…In terms of the comparability of the base population, our study cases had profiles for sex, age and rural/urban distribution similar to the cases reported by the Gharbiah Cancer Registry [7]. While our study did not reveal a relationship between aflatoxin exposure and liver cancer risk, previous studies from Egypt had shown a high level of aflatoxin in the food and samples of liver cancer patients [58][59][60][61][62][63]. Future studies should continue to investigate the role of aflatoxin in relation to other risk factors for liver cancer in Egypt.…”
Section: Discussionsupporting
confidence: 66%
“…In terms of the comparability of the base population, our study cases had profiles for sex, age and rural/urban distribution similar to the cases reported by the Gharbiah Cancer Registry [7]. While our study did not reveal a relationship between aflatoxin exposure and liver cancer risk, previous studies from Egypt had shown a high level of aflatoxin in the food and samples of liver cancer patients [58][59][60][61][62][63]. Future studies should continue to investigate the role of aflatoxin in relation to other risk factors for liver cancer in Egypt.…”
Section: Discussionsupporting
confidence: 66%
“…Single, double, and triple asterisks indicate sensitivity < 30× C max , < 10× C max , and < 1× C max , respectively. C max or exposure values were obtained from the following references: APAP, 700 µ M (Vale and Proudfoot, 1995); aflatoxin B1, 0.03 µ M (Hassan et al, 2006); amiodarone, 3.9 µ M (Regenthal et al, 1999); chlorpromazine, 1.6 µ M, (Regenthal et al, 1999); troglitazone, 2.82 µ M (Loi et al, 1999); and ximelagatran, 0.3 µ M, (Schützer et al, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…PHH spheroids were the most sensitive system in the acute as well as chronic setting, indicating toxicity at exposure levels detected in exposed individuals (28.5 nM; Hassan et al, 2006), followed by HepaRG cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on human serum samples mostly have limited sample sizes compared with the current study. In a study performed by Hassan et al (35) , the researchers measured the AFB 1 levels in the serum and milk of mothers (n 50) and serum of infants (n 50) in Egypt. Twenty-four out of fifty mothers and their infants had been contaminated with AF with the following mean contamination levels: 8?9 (SD 4?2) ng/ml (mothers' serum), 1?9 (SD 0?6) ng/ml (mothers' milk) and 1?8 (SD 0?9) ng/ml (infants' serum).…”
Section: Discussionmentioning
confidence: 99%